Late Paleocene fishes of the Ravenscrag Formation, Roche Percée area, southeastern Saskatchewan, Canada. Issue 3 (4th May 2021) - Sinha, Sinjini; Brinkman, Donald B.; Murray, Alison M.; Krause, David W.
ABSTRACT: The diversity of fishes represented in upper Paleocene microfossil localities in the Ravenscrag Formation near Roche Percée, Saskatchewan, is documented. Thirteen kinds of fishes are recognized. Two chondrosteans are present, a sturgeon and a paddlefish, both represented by small, irregularly shaped, ornamented bony plates. Four kinds of basal neopterygians are identified. Two of these, Atractosteus and Cyclurus, are widely distributed in both Paleocene and Upper Cretaceous localities. The remaining two are unnamed taxa designated Holostean A and Holostean B that were known previously from Upper Cretaceous localities but have not been reported from the Paleocene prior to this report. The presence of these taxa in the late Paleocene further supports the conclusion that basal neopterygians were little affected by the K/Pg mass extinction event. Seven teleosts are present in the assemblage. This assemblage of teleosts is similar to assemblages of upper Paleocene fishes from the Paskapoo Formation of Alberta in the presence of osteoglossomorphs, a gonorhynchiform, the esocid Esox, a percopsiform, and at least one other acanthomorph. It differs in the presence of a generically indeterminate protacanthopterygian designated here as morphotype ES-1 and a teleost of uncertain relationships designated morphotype PT-1. Neither of these taxa is present in the Late Cretaceous, suggesting that they first appeared in the area during the early or middle Paleocene. Comparison of the fish assemblages of the late Paleocene and early Eocene suggests that a major faunal transition occurred at the Paleocene/Eocene boundary, and that this involved a decrease in diversity of basal neopterygians.